Efeito da irradiação do método de facilitação neuromuscular proprioceptiva em indivíduos hemiplégicos pós-acidente vascular encefálico: evidências eletromiográficas - RAIMUNDO, Karoline Cipriano (2014)
One of the most important impairment after stroke is hemiplegia, which is characterized initially by a total absence of movement. And six months post event (chronic phase) individuals might present muscular hypertonia, flexor posture of the upper limb and extensor of the inferior one, with functional limitation. It is thought to stimulate the affected limb by the use of the contralateral preserved one, thus activating the plegic muscles. The objective of this paper was to evaluate the immediate effect of the application of the irradiation procedure of the Proprioceptive Neuromuscular Facilitation (FNP) in the muscles of the plegic upper limb in acute and chronic post stroke patients. Twenty-two individuals were included in this study (6 acute stroke group- GA, 8 chronic stroke group- GAC and 8 control group- GC), mean age 57,16 ± 10,98 years for GA, 54,13 ± 8,26 years for GAC e 56,65 ± 10,12 years for GC. Stroke participants were evaluated through a record containing their personal and disease data, ICF scale, Fugl-Meyer Assessment Scale and both group were submitted to an electromyography evaluation of the muscles posterior deltoid (DP), anterior deltoid (DA), pectoralis major (PM) and external oblique (OE) in 4 different positions. The mean Fugl-Meyer Score for GA was 15,33 ± 3,55 for the motor function items and 43,83 ± 5,1 for Range of Movement and Pain and for GAC scored a mean value of 12,62 ± 14,7 for the motor function items and 40 ± 5,5 for Range of Movement and Pain. ICF classified as moderate to severe the items referent to motor and cognitive alterations and activities of daily living. Electromyography evidenced significant differences between the groups and positions of the assessed muscles, on regards to the rest position, which suggests that the muscles from the plegic upper limb are activated during the use of the inferior limb diagonal. It can be concluded that irradiation for post stroke patients in an acute and chronic phase is important for the activation of the plegic upper limb muscles, mainly DP, DA and OE both contralateral to the diagonal (affected limb) and ispilateral to the diagonal.